2016
DOI: 10.1097/ccm.0000000000001717
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Noble Gases in the Attenuation of Ischemia Reperfusion Injury: A Systematic Review and Meta-Analyses

Abstract: Helium and xenon show organ protective effects mostly in small animal ischemia reperfusion injury models. Additional information on timing, dosing, and comparative efficacy of the different noble gases, as well as confirmation in large animal models, is needed before designing clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 103 publications
(130 reference statements)
1
31
2
Order By: Relevance
“…The exact mechanisms underlying noble gas‐induced organ protection remain largely obscure, but most likely involve anti‐inflammatory and prosurvival mechanisms. As an example, xenon has been demonstrated to activate HIF‐1α and its downstream effectors, including erythropoietin and VEGF, in rodents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact mechanisms underlying noble gas‐induced organ protection remain largely obscure, but most likely involve anti‐inflammatory and prosurvival mechanisms. As an example, xenon has been demonstrated to activate HIF‐1α and its downstream effectors, including erythropoietin and VEGF, in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could suggest that noble gases might have different molecular effects in small and large animals that might have contributed to the lack of clinical effects of argon and xenon in this model. Indeed, only a few studies have examined the effects of these noble gases in large‐animal models, and found the organ‐protective effects of noble gases to be less obvious in large compared with small animals. Moreover, reported results in pigs are contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xenon has been demonstrated to have only minimal hemodynamic side effects when compared to commonly used intravenous or inhalational anesthetics . Moreover, xenon conveys neuroprotection in preclinical models of neonatal asphyxia and anesthesia‐induced neurotoxicity …”
Section: Introductionmentioning
confidence: 99%